2023
DOI: 10.2174/1389557523666221116154907
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal, Liver, Pancreas, Oral and Psychological Long-term Symptoms of COVID-19 After Recovery: A Review

Abstract: Abstracts: Due to the importance of control and prevention of COVID-19-correlated long-term symptoms, the present review article has summarized what has been currently known regarding the molecular and cellular mechanisms linking COVID-19 to important long-term complications including psychological complications, liver and gastrointestinal manifestations, oral signs as well as even diabetes. COVID-19 can directly affect the body cells through their Angiotensin-converting enzyme 2 [ACE-2] to induce inflammatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 131 publications
0
4
0
Order By: Relevance
“…Interestingly, we found that GI symptoms were most severe during the acute phase of the infection, and the symptoms began to improve in the first month of follow-up. Liver injuries occur in 14–53% of COVID-19 cases ( 13 ). Cooper S. et al ( 14 ) reported that in children with COVID-19, possible long-term liver complications include acute liver failure and hepatitis with cholestasis, noting that unlike adult cohorts, the pediatric cohort did not exhibit steatosis.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we found that GI symptoms were most severe during the acute phase of the infection, and the symptoms began to improve in the first month of follow-up. Liver injuries occur in 14–53% of COVID-19 cases ( 13 ). Cooper S. et al ( 14 ) reported that in children with COVID-19, possible long-term liver complications include acute liver failure and hepatitis with cholestasis, noting that unlike adult cohorts, the pediatric cohort did not exhibit steatosis.…”
Section: Discussionmentioning
confidence: 99%
“…Digestive outcomes were selected mainly based on evidence in prior literature and the data on digestive system disease records in the UK Biobank [ 2 , 8 , 14 , 21 24 ]. As shown in Additional file 1 : Table S2, all the outcomes were defined based on the 10th revision of the International Classification of Diseases (ICD-10).…”
Section: Methodsmentioning
confidence: 99%
“…It should also be noted that gastrointestinal symptoms such as nausea, vomiting, and diarrhea present during hospitalization for SARS-CoV-2 infection can lead to malnutrition, which has been linked to increased mortality in patients with COVID-19 [ 66 , 67 ]. Nutrition plays a fundamental role not only during hospitalization but also in reducing gastrointestinal sequelae.…”
Section: Gastrointestinal Domainmentioning
confidence: 99%